Manajemen Produktivitas Ilmiah Dosen STAI Al-Hidayah Bogor Tahun 2020-2024 yang Terindeks dalam Google Scholar: Scientific Productivity Management of STAI Al-Hidayah Bogor Lecturers 2020-2024 Indexed in Google Scholar - Rahendra Maya; Samsuddin, Samsuddin; Muhammad Fadilah Alfarisi (TARBIYAH: Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to determine the productivity of STAI Al-Hidayah Bogor lecturer from 2020 to June 2024 in writing scientific papers and publishing them until they are indexed in Google Scholar and analyzing them based on management perspective, especially in research management. This is based on the rationality that the publication of scientific works has now become evidence of increasing the quality of education in higher education, both from the functional career of individual lecturer, as well as in increasing the accreditation of their study programs/tertiary institutions. This reseach uses quatitative research to collect initial data about lecturers’ scientific productivity and qualitative research to analyze it descriptively-interpretively until conclusions are drawn. Especially in the management aspect. The results of the research show that in the last five years there has been a decline in the number of scientific works published by STAI Al-Hidayah Bogor lecturers in various national journals until they are indexed in Google Scholar. It can also be seen that there is a high gap in scientific productivity beetwen STAI Al-Hidayah Bogor lecturers in the number of documents, citation, i-index, and i10-index as well ad in their productivity as first authors, both as sole authors individually and as first authors collaboratively. This requires the implementation of scientific productivity management by lecturers in managing their research, which includes planning, implementing, controlling, monitoring, evaluating, and reporting research activities.